Их Монгол гүрний төрийн байгуулалт: анхны холбооны улсын загвар - Ц.Батболд (Politology, 2024)
This paper shows that scientists &scholarlars works and studies which based on historical source, history of the State Development of Great Mongolian Empire in XIII century. As a result of this study, to make evidences and examples around the federal structure of the model, to approve based on assumptions proved facts that created the State structures in the world first time. The Framework of study political system Mongolian States (1206-1227); Great Mongolian Empire (1229- 1260); The decomposition of Great Mongolian Empire & Yuan Dynasty (1261-1368) which could be determined to divide into three phases. Main goal of this paper is to report the Mongolian State’s structures newly togive its valuables make conclusion. Three main studies posted in this study. First, the studied State’s structure &system of Great Mongolian Empire. Secondly, Modern new state structures of other countries have been analyzed based on empirical facts of Great Mongolian dynasties & State environment which were based on 7 basis the federal government arrangements. Third, to determine the how to provide state sustainable situations of State when the right political struggle for power between 1241-1246, the goal was to clarify was how to maintain political stability. As a result of the comparison studies: First, Great Mongolian dynasties were government ministries with patrimoniali bureaucratic apparatus. Second, Great Mongolian Empire existed between 1229-1260 that was a federal model. Third, it could made conclusions which shows the state development communication model and state administrative apparatus political stabilitythat could satisfy without "Great King" for 10 years. Товч агуулга: ХІІІ зуунд тухайлбал, 1229-1260 оны үеийн Их Монгол гүрний төрийн байгуулалт холбооны улсын загвартай байсныг нотлох баримтуудаар тодорхойлсон. Илтгэлийн гол зорилго 1229-1260 онд оршиж байсан Их Монгол гүрний төрийн байгуулалтыг шинээр харж, үнэлэлт дүгнэлт өгөхөд чиглэгдсэн. Энэ хүрээнд дараах гурван үндсэн зорилго тавьсан. Нэгд, Их Монгол гүрний төрийн тогтолцооны онцлог. Хоёрт, орчин үеийн холбооны төрийн байгуулалттай улсуудын үндсэн шинжүүдийг Их Монгол гүрний төрийн байгуулалттай холбоотой эмпирик баримтуудад тулгуурлан харьцуулах. Гуравт, 1241-1246, 1248-1251 оны хооронд болсон эрх мэдлийн төлөөх улс төрийн их тэмцлийн үед Их Монгол гүрний патримониаль бюрократ тогтолцоо төрийн тогтвортой байдлыг хэрхэн хадгалж байсныг тодруулах зорилго тавьсан.